Investor responses to information updates on peer behavior and public investment policy: The case of green investments - Marius Alt; Marius Berger; Johannes Bersch (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Green startups are a major driver of eco-innovation and as such a major contributor to climate change mitigation and green growth. However, they often lack sufficient funding from investors. Our study focuses on the factors that determine venture capital investors to invest in green startups. In particular, we analyze how information about i) the investments into green startups of other investors and ii) investment provision by public institutions affect the willingness of investors to act accordingly. We combine data from an online survey with angel investors comprising a discrete choice experiment and data from the Mannheim Enterprise Panel. Our findings show that the expectation of future demand for green products and the environmental attitudes of investors can explain whether investors engage in the energy industry. Regarding the effect of information provision, we find that investors strongly respond to information on both investments in green startups by other investors and public investment in green startups. However, in both cases, investors reduce their investments in green startups after receiving the information. We show that this is due to investors largely overestimating the share of investments in green startups by others and due to a crowding out of private investment by investments of public institutions.
Keywords: G11; Q56; M14; G02; A13; C25; 330; Sustainable investments; Venture capital; Belief updating; Discrete choice experiment; Panel data